2020
DOI: 10.1186/s40068-020-00174-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of soybean to Rhizobial inoculation and starter N fertilizer on Nitisols of Assosa and Begi areas, Western Ethiopia

Abstract: Background: For manipulating N 2 fixation and improve the N benefits to agricultural legumes, there is a need to reduce the inhibitory effect of applied N on Rhizobia inoculant. The optimum level of inorganic N as starter fertilizer with inoculation of Rhizobia is essential to increase the production of legumes in smallholder farmers. However, the effect of inorganic N level which should be used by farmers with an inoculation to increase the production of soybean is not yet well known in soils of western Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Higher NP and NG were obtained under treatment with fertilizers supplied with S. These yield-related parameters might be attributed to seed yield per plant so the yield value of S-supplied plants is higher. Prior studies have indicated that the combination of fertilization and the application of a suitable rhizobium strain may represent a more effective agronomic strategy for achieving high yields in soybean cultivation [32,33]. In this study, a phenomenon was confirmed.…”
Section: The Influence Of Sulfur and Rhizobium Inoculation On Soybean...supporting
confidence: 67%
“…Higher NP and NG were obtained under treatment with fertilizers supplied with S. These yield-related parameters might be attributed to seed yield per plant so the yield value of S-supplied plants is higher. Prior studies have indicated that the combination of fertilization and the application of a suitable rhizobium strain may represent a more effective agronomic strategy for achieving high yields in soybean cultivation [32,33]. In this study, a phenomenon was confirmed.…”
Section: The Influence Of Sulfur and Rhizobium Inoculation On Soybean...supporting
confidence: 67%
“…For instance, Agoyi et al [9] tested 65 genotypes for their response to inoculation and reported significant differences in the number of nodules, effective nodules, and fresh and dry nodule weight among genotypes. Inoculation of soybean with Rhizobia significantly improved nodule number [10] and nodule dry weight [11]. Moreover, Argaw [12] reported that the response of soybean genotypes to inoculation with the same strain significantly affected nodule number and nodule dry weight under both field and greenhouse conditions.…”
Section: Introductionmentioning
confidence: 97%